Do actively managed equity funds outperform their passively managed counterparts? Evidence from Indonesia, South Korea and Turkey - Schweers, Oliver (2013)
One important implication of the Efficient Market Hypothesis is that there is no additional value in engaging in active portfolio management processes since all stocks should be trading at their fair prices in a fully efficient market. In fact, there is a large amount of empirical evidence providing support for the validity of this implication, in particular in the US and European markets. This study examines whether superior risk-adjusted performance can be generated by active portfolio managers compared to their passive counterparts in less liquid and efficient markets such as Indonesia, South Korea and Turkey. The performance is evaluated by applying Sharpe’s ratio, Treynor’s measure and Jensen’s alpha. Irrespective of the country and the technique employed there is no evidence for the performance of active and passive investment approaches to be significantly different from each other. This conclusion holds both before and after management fees are taken into account. Moreover, the findings do not provide evidence for existence of informational advantage of domestic investment managers since there is no significant difference in the performance generated by domestic and international funds.